Quality Contingent Contracts : Evidence from Tanzania's Coffee Market - Mahdi, Shireen (World Bank, Washington, DC, 2012)
The literature on product quality in markets where product attributes are not readily observable indicates that information asymmetries and incentive problems may lead to the under-provision of quality. This paper contributes to this literature by estimating the effects of village-level contractual arrangements on producer incomes and on quality enhancing production practices. Three contract types are studied: spot contracts, contingent contracts with product grading and contingent contracts without product grading. To do this, the study uses original data from a survey of 450 coffee producers in Tanzania's coffee market that take advantage of contractual variation in the Kilimanjaro region. The results indicate that coffee contracts that include village-based product grading have a large positive effect on producer incomes, and that the grading effect is associated with production practices that enhance quality. The results also indicate that cooperative membership has no significant effect on producer incomes.